Sikap guru Pendidikan Khas integrasi bermasalah pembelajaran terhadap perkhidmatan bimbingan dan kaunseling. - Mohd. Ibrahim, Nur Liyana; Ahmad, Jamaludin (Jabatan Perkhidmatan Awam Malaysia, 2008)
The purpose of the research is to know how the teachers of special education of learning disability integration react towards the guidance and counseling services. The descriptive survey uses questionnaires of 'Counseling Attitude Scales' which is translated into Malaysian language and the validity and reliability is acknowledged by Awang Mat Ali (1979). The subject of the survey consists of 109 teachers from special education integrated with learning disability department. They are randomly selected from 10 schools in the district of Hulu Langat, Selangor. The primary survey has been carried out and later is key-in in the SPPS 12.0 version. The accountability of the survey is Cronbach Alpha 0.702. The data is analyses using t - test and A3OVA test. The outcome of the descriptive survey is there is no significant difference between gender and attitude, with value t (109) = .531, p > 0.05. Also among the Malay, Chinese and Indian ethnics, there is no different in their behavior on how they reacts towards the guidance and counseling services F = 4.234, p < 0.05. In fact, there is no significant difference between the duration of services with the diploma holders t (40) = 1.170, p > 0.05 and degree holders t(65) = .766, p > 0.05. In conclusion, the outcome indicates that the majority of these teachers react positively. Based on the finding, the need of guidance and counseling services in the school of special education integration with learning disability is strong recommended in order to upgrade the overall quality of the guidance and counseling in the school.